Sanchez Works Featured at Gallery (Raton, NM Raton Range, 1997)
Article is about Kathy Sanchez and her art work being displayed at the Old Pass Gallery.
Newspaper article
Master list item # 121
File location is in the Raton file Cabinet
Keywords: Sanchez, Kathy -- Artist; Old Pass Gallery; New Mexico Arts -- Sponsor; McCune Foundation -- Sponsor; Art Exhibits; Art Promotion; Native American Art; Raton, New Mexico